(untitled) (Trabalho & Educação, 2016)
In this research, we investigated the rap symbolic function to analyze how young Brazilian and French rappers within the universe created by this artistic expression, use and manipulate symbols to represent themselves in the reality, but also to act on it, operating displacements to produce an effect on the imaginary associated with these young people. We were to meet young Brazilian and French rappers to investigate what they think, what they feel, and how they act in social reality, at the crossroads between what is socially established and subjectively lived. Rap is viewed as an analyzer of these youths, allowing us to apprehend their singularities, the context in which they live, and how they share their experiences through this art form. This paper discusses the process of deconstruction and reconstruction operated in our object of research, often neglected by scientific studies. Clinical epistemology invites you to explore it as a heuristic element of the research. We analyze the processes of implications and distance in regard as the object of research, that emerges at two different times: during the field, in meeting its object, and during writing, which takes place in the après-coup of the research. ___ Em nosso trabalho, investigamos a função simbólica do rap para analisar como os jovens rappers brasileiros e franceses, no interior do universo criado por essa expressão artística, utilizam e manipulam símbolos para se representar na realidade, mas também para agir sobre ela, operando deslocamentos que produzirão uma incidência no imaginário associado a esses jovens. Fomos ao encontro de jovens rappers brasileiros e franceses para investigar o que pensam, o que sentem e como agem na realidade social, na encruzilhada entre o que é socialmente estabelecido e subjetivamente vivido. O rap é tomado como um analisador dessas juventudes, permitindo-nos apreender singularidades locais, do contexto onde vivem, e como compartilham suas experiências por meio dessa manifestação artística. Neste artigo discutimos os processos de desconstrução e reconstrução operados em nosso objeto de estudo, frequentemente calados pelos trabalhos científicos, e que a epistemologia clínica convida a explorar como elementos heurísticos da pesquisa. Analisaremos os movimentos de implicação e distanciamento da pesquisadora, que emergem em dois momentos diferentes: durante a realização de campo, no encontro com seu objeto, e durante a escrita, que se realiza no après-coup da pesquisa.